TIME ADJUNCT AND ITS TRANSLATION FOUND IN THE MRS. VETERINARY AND DOCTOR SUHARKO - Juliarta, I Made; Suardana, Putu Eka (International Journal of English Learning and Applied Linguistics (IJELAL), 2024)
This research study focuses on Time Adjunct and their translations into Indonesian found in thestory entitled “Mrs. Veterinary and Doctor Suharko”. This study aims to find out the forms of timeadjunct found in the story entitled “Mrs. Veterinary and Doctor Suharko” and the types of translationshifts occurred. The process of analyzing the data started by reading the entire data source, thencontinued by gaining the data in the form of time adjunct and the last step was identifying thetranslation shift found. The result of this research indicated that most English time adjunct wastranslated into Indonesian using the theory of translation shifts proposed by Catford. There aresixteen data of time adjuncts found in the data source.